Profil Kepercayaan Diri (Self Confidence) Remaja di Panti Asuhan Aisiyah Pasar Bawah - Latifa Khairani; Elviana Elviana; Riza Sri Putri (Journal Innovation In Education, 2024)
The focus of this research is to determine the self-confidence profile of adolescents at the Aisiyah Pasar Bawah Orphanage. This research was conducted on teenagers at the Aisiyah Pasar Bawah Orphanage. This research is descriptive qualitative research. So in analyzing the data the author uses qualitative descriptive methods. As for collecting data, the author used literature studies (as a theoretical basis) and field studies using observation and interview methods. To answer this problem thoroughly and in depth, the method used in this research is a qualitative method, the analysis technique uses descriptive techniques. The form of the self-confidence profile of teenagers at the Aisiyah Pasar Bawah Orphanage is in the form of individual abilities. There are several individuals who can display their talents and can realize their interests in public, but there are also some individuals who are less able to assess themselves. Individuals consider themselves unable to do something well, such as lacking the courage to express opinions, feeling inferior and afraid of answering questions incorrectly and lacking the ability to actualize themselves to the maximum. Some individuals also have doubts and some bad prejudices about their future, where they think whether their future journey will go according to their expectations.